Encapsulation of power electronics components for operation in harsh environments - Stosur Mariusz; Sowa Kacper; Piasecki Wojciech; Płatek Robert; Balcerek Przemysław (Archives of Electrical Engineering, 2017)
This paper reports on analyses and testing of sensitive power electronics components encapsulation concept, enabling operation in harsh, especially high pressure environments. The paper describes development of the concept of epoxy modules that can be used for protecting of the power electronics components against harsh environmental conditions. It covers modeling of the protective capsules using a simple analytical approach and Finite Element Method (FEM) models and validation of the developed models with the high pressure tests on samples fabricated. The analyses covered two types of the epoxy modules: of sphere- and elongated- shape, both with electrical penetrators that enable electrical connection of the encapsulated components with external power sources as well as other power modules and components. The tests were conducted in a pressure chamber, with a maximum applied pressure of 310 bars, for which online strain measurements have been conducted. The experimental results were compared with the simulation results obtained with analytical and FEM models, providing validation of the models employed. The experimental part of this work was conducted in collaboration with Polish Naval Academy in Gdynia.